Switching from telephone to web‐first mixed‐mode data collection: Results from the Transition into Adulthood Supplement to the US Panel Study of Income Dynamics. (27th April 2022) - Sastry, Narayan; McGonagle, Katherine A.
Abstract: We conducted an experiment to evaluate the effects on fieldwork outcomes and interview mode of switching to a web‐first mixed‐mode data collection design (self‐administered web interview and interviewer‐administered telephone interview) from a telephone‐only design. We examine whether the mixed‐mode option leads to better survey outcomes, based on response rates, fieldwork outcomes, interview quality and costs. We also examine respondent characteristics associated with completing a web interview rather than a telephone interview. Our mode experiment study was conducted in the 2019 wave of the Transition into Adulthood Supplement (TAS) to the US Panel Study of Income Dynamics (PSID). TAS collects information biennially from approximately 3, 000 young adults in PSID families. The shift to a mixed‐mode design for TAS was aimed at reducing costs and increasing respondent cooperation. We found that for mixed‐mode cases compared to telephone only cases, response rates were higher, interviews were completed faster and with lower effort, the quality of the interview data appeared better, and fieldwork costs were lower. A clear set of respondent characteristics reflecting demographic and socioeconomic characteristics, technology availability and use, time use, and psychological health were associated with completing a web interview rather than a telephone interview.